Lessons learned from the pre-implementation phase of a patient navigation intervention to increase patient portal enrollment in Federally Qualified Health Centers - Matthews, Alicia K.; Elkefi, Safa; George, Maureen; Cassells, Andrea; Tobin, Jonathan N. (Frontiers in Health Services, 2025)
ObjectivesTo describe the pre-implementation phase of a patient navigator-led intervention to increase patient portal enrollment among adults receiving care within Federally Qualified Health Centers (FQHCs) in New York City.MethodsWe conducted semi-structured in-depth interviews with fourteen key stakeholders (clinicians, nurses, patient navigators, and practice staff) in three FQHCs. Using the Exploration, Preparation, Implementation, and Sustainment (EPIS) framework as a guide, the interviews focused on current patient portal education and enrollment procedures, establishing the workflow for the new patient navigator-led enrollment intervention, co-creation of low-health literacy educational materials, and identifying potential challenges and mitigation strategies. Thematic analysis was conducted to inform the development of a standardized patient portal enrollment protocol.ResultsFindings revealed significant variability in support and educational procedures across the three FQHC locations. Strategies that emerged as potentially effective for integrating patient navigators into the center workflow included scheduling navigators during peak hours (Mondays to Thursdays, 10 AM to 4 PM) and positioning them in high-traffic areas such as waiting rooms. Customizing educational materials to meet linguistic and cultural needs was important for improving accessibility and relevance. Providing navigators with access to the appointment scheduling and Electronic Health Records (EHR) systems was viewed as enabling real-time identification and engagement of eligible patients, reducing missed enrollment opportunities. Proactive engagement methods, including in-lobby interactions, were viewed as essential in fostering sustained portal usage. Addressing technological barriers and language challenges through multilingual resources and hands-on demonstrations was also described as creating a more inclusive environment.ConclusionsThe study results have implications for implementing and evaluating a patient navigator-led intervention to increase patient portal enrollment among patients in FQHCs. Hiring and training dedicated navigators, customizing educational materials, and integrating navigators into the practice's workflow are key strategies for improving the adoption of this intervention. The findings provide a foundation for future research to evaluate the effectiveness, sustainability and scalability of the intervention approach across diverse healthcare settings.